Shift in Parenting Roles and Anti-Social Behaviour in the Classroom: The Case of Adolescents in Public Secondary Schools in Bamenda III, Mezam Division - Achiri, Lum Bobga Jacqueline (International Journal of Formal Education, 2024)
The study examined the relationship between shift in parenting roles and adolescent antisocial behaviour in the classroom among students in Secondary Schools in Tubah. Specifically, the study addressed how absence of parents from home and how transfer of parenting roles to nannies or “house helps” influences adolescent antisocial behaviors in the classroom in secondary schools in Tubah. The social learning theory of Bandura and the Psychosocial theory of Erikson were used. The survey research design was used and the sample of 250 students was drawn using simple random sampling technique. Both descriptive and inferential statistics were used to analysed the data, where mean and standard deviation were used to answer the research questions while the simple regression analysis was conducted to verify the null hypothesis in order to determine the relationship between the variables. Based on the results pertaining to the two research questions; firstly, findings indicated that there exists a significant positive relationship between absent of parents from homes and adolescents’ anti-social behaviours in the classroom, p-value = 0.000, p < 0.05. It was also identified that 37.20% of the variation in adolescent anti-social behaviour can be accounted for by the absence of their parents from home which leaves them struggling with emotional and mental challenges. Secondly, findings also showed that, there exists a significant positive relationship between transfer of parental roles to nannies and adolescents’ anti-social behaviours in the classroom, p-value = 0.000, p < 0.05. I was also, further revealed that 53.40% of the variance in adolescent antisocial behaviours can be explained by the transfer of parental roles to nannies, which makes them develop lack of emotional attachment, self-esteem and a sense of belonging. Based on these findings it was concluded that, shift in parental roles have significant effect on adolescent anti-social behaviours, hence it was recommended that, parents should create and spend adequate time with their children and avoid transferring all roles to nannies or “House help”.